Short forms of the Body Appreciation Scale-2 (BAS-2SF): Item selection and psychometric evaluation. (June 2022) - Tylka, Tracy L.; Linardon, Jake; Wood-Barcalow, Nichole L.; Daníelsdóttir, Sigrún; Fuller-Tyszkiewicz, Matthew
Abstract: The 10-item Body Appreciation Scale-2 (BAS-2; Tylka & Wood-Barcalow, 2015) is a widely used contemporary measure of positive body image that assesses one's love for, acceptance and appreciation of, and respect for their body. Given the need for abbreviated measures to reduce participant burden and study cost, we aimed to generate a short form of the BAS-2 (BAS-2SF). Two versions of the BAS-2SF emerged: a 3-item version derived deductively from theory (items selected based on their unique contribution to the body appreciation construct), and a 2-item version generated empirically (items selected based on a genetic algorithm approach). Psychometric evidence was garnered across five studies, totaling 3114 participants. Both BAS-2SF versions correlated highly ( r s = .93–.97) with the original 10-item BAS-2 and demonstrated internally consistent and stable scores. Factor analyses revealed high item-factor loadings, unidimensionality, and gender invariance of the 3-item BAS-2SF. Correlations with construct validity measures, as well as model pathways, were similar between both BAS-2SF versions and the 10-item BAS-2. BAS-2SF versions also evidenced incremental validity. Both BAS-2SF versions retain the psychometric integrity of the BAS-2 and are recommended for use; however, the 3-item BAS-2SF is an ideal option for researchers who wish to estimate a body appreciation latent factor. Highlights: A 2-item short form of the BAS-2 emerged via empirical (genetic algorithm) analysis. A 3-item short form of the BAS-2 was derived deductively from theory. Across five studies, both short forms correlated very highly with the 10-item BAS-2. Both forms demonstrated internally consistent and stable scores, gender invariance, and construct, discriminant, and incremental validity. Five studies suggested that a BAS-2 short form can be used in lieu of the full-length BAS-2.